2004
DOI: 10.1121/1.1738452
|View full text |Cite
|
Sign up to set email alerts
|

Variability of low frequency sound transmission measurements

Abstract: In this paper we discuss the characterization of low frequency sound transmission between two rooms via a flexible panel. A fully-coupled modal model is used to investigate the individual effect of the source room and the receiving room on the measured sound reduction index, and the results are compared with the ideal case of having a free field on both sides of the panel. The effect of the source room on the measured sound reduction index at low frequencies can be reduced by using a number of suitable-driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…10 The formulation can be readily extended to the synthesis of any random pressure field with prescribed spatial correlation properties as long as the pressure excitations we aim to reproduce are modeled as random processes stationary both in space and time. The general synthesis method is now briefly summarized.…”
Section: A the Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The formulation can be readily extended to the synthesis of any random pressure field with prescribed spatial correlation properties as long as the pressure excitations we aim to reproduce are modeled as random processes stationary both in space and time. The general synthesis method is now briefly summarized.…”
Section: A the Synthesis Methodsmentioning
confidence: 99%
“…This variability has been widely studied experimentally through interlaboratory comparisons 3,4 as well as through analytical [5][6][7] and numerical 8,9 investigations. In order to make the measurement of the incident power more reliable at low frequencies, Bravo and Elliott 10 have proposed a novel approach based on the reconstruction of the statistical properties of an acoustic diffuse field over the surface of a test partition using a near-field array of suitably driven loudspeakers. Theoretical results have shown that this approach is efficient in providing a measure of the sound reduction index that only depends on the properties of the panel itself and, at this stage, it would benefit from experimental validations.…”
Section: Introductionmentioning
confidence: 99%
“…The diffuse field assumption is only valid in medium and high frequency ranges, as the sound field at low frequencies is dominated by few normal modes in reverberation chamber (Schroeder, 1996). The recommendation included in annex in ISO 140-3 (1995) to increase the distance between microphone position and room boundaries and sampling of sound field, increasing the number of loudspeaker positions, the averaging time and use of absorbing materials to decrease the reverberation time still becomes inadequate to enhance the reproducibility of results below 100 Hz (Bravo, Elliott, 2004;Roland, 1995;Pedersen et al, 2000). If room volume differs by about 40%, the predicted sound insulation could differ by alteast 3 dB (Maluski, Gibbs, 2000).…”
Section: Low Frequency Diffusion Issuementioning
confidence: 99%
“…If room volume differs by about 40%, the predicted sound insulation could differ by alteast 3 dB (Maluski, Gibbs, 2000). Some studies (Bravo, Elliott, 2004) have tried to investigate about reducing the effect of source room on measured sound reduction index at low frequencies by using a number of suitable driven loudspeakers close to the panel to stimulate a diffuse incident field. The low frequency diffusion is a cumbersome task achieved by scientifically selecting the volume, surface area of reverberation chamber and enhancing the state of diffusion for reducing the spatial variance in the value of sound pressure level and reverberation time observed at various positions in the room.…”
Section: Low Frequency Diffusion Issuementioning
confidence: 99%
“…In [3] two situations are compared. On the one hand panels placed in an infinite baffle, separating semi-infinite acoustic domains.…”
Section: Introductionmentioning
confidence: 99%